Perancangan Klaster Server Web Dengan Availabilitas Tinggi Menggunakan Teknologi Failover, Load Balancing dan Distributed File System - Tiara Erlinda; Mahendra Data; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The developments of World Wide Web (WWW) technology has an impact on the increasing website every day. The use of the web for everyday life is very influential for various aspects of life such as to communicate, entertainment, and education. It takes a system that has a high availability level to operate continuously and ensures no failure so that the system can provide continuous service without interruption to the user. The researcher's solution is to design a high availability web server cluster with failover technology using Keepalived. There is also load balancing technology using Varnish which supports distributing workloads to web servers and distributed file systems using GlusterFS to share files between servers. The study was conducted using LAMP server ie Linux Apache, MySql and PHP. Apache server is assigned as web server. Testing is done in terms of downtime, throughput, CPU usage, memory usage and functional. The results of the research found that the value of downtime with an average of 1 second when the main server is dead. The highest throughput value for the connection is obtained when the number of connections is 40 and the lowest when the number of connections is 100. The usage and memory usage values ​​increase up to 68.3% for CPU and 65.5% for memory depending on the number of connections. The result from functional test proved that the system is running according to its function. Based on these results, this system can be a solution for systems that require high availability.